Persons with Disabilities and Coronavirus Disease (COVID-19) in Latin America and the Caribbean: Status and Guidelines - Economic Commission for Latin America; the Caribbean (United Nations, 2020)
In the context of the global coronavirus disease (COVID-19) pandemic, the Economic Commission for Latin America and the Caribbean (ECLAC) is preparing a series of short publications with relevant policy recommendations for this period. This note offers a number of recommendations to address the impact of COVID-19 on persons with disabilities in the region.